Applying Quality Improvement Approaches to Reduce Mother-to-Child HIV Transmission and Improve Health and Nutrition Care in Five Countries: Lessons from the Partnership for HIV-Free Survival. (10th June 2019) - Stern, Amy F.; Ismail, Anisa; Karamagi, Esther; Nsubuga-Nyombi, Tamara; Mwita, Stella Kasindi; Ngonyani, Monica M.; Kinyua, Kevin; Muange, Prisca; Lerotholi, Kelello L. M.; Rantekoa, Manone; Mahlalefa, Khotso G.; Tshabalala, Maureen Fatsani; et al.
The World Health Organization guidelines for treating pregnant HIV-positive women and preventing HIV transmission to infants now recommend lifelong antiretroviral treatment for pregnant and breastfeeding women. We applied quality improvement (QI) methods to support governments and facility staff to address service gaps in 5 countries under the Partnership for HIV-Free Survival (PHFS). We used 3 key strategies: break the complex problem of improving HIV-free survival into more easily implementable phases, support a national management team to oversee the project, and support facility-level staff to learn and apply QI methods to reducing mother-to-child transmission. The key results in each country were increases in data completeness and accuracy, increases in retention in care of mother–baby pairs (MBPs), increase in coverage of MBPs with appropriate services, and reduction in vertical transmission of HIV. The PHFS experience offers a model that other multicountry networks can adopt to improve service delivery and quality of care.